ANALISIS DAN PERANCANGNAN ARSITEKTUR TEKNOLOGI PADA PERGURUAN TINGGI MENGGUNAKAN FRAMEWORK TOGAF - M Khairul Anam; Rivaldi Dwi Andhika; Khusaeri Andesa; Herwin Herwin; Agustin Agustin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
In general, higher education is divided into two categories of benefits from the application of Information and Communication Technology (ICT). The first is referred to as core values and supporting values. The computer network at STMIK Amik Riau currently uses the Telkom Speedy Wireless Network provider in each building. Then each student is only given 1 account to access the Hotspot network on the STMIK Amik Riau campus which can only be used on 1 laptop that is registered and capacity that has been limited or shared by network operators. However, the use of Hotspots that students want to access is only found in a few places which if used are smooth. To overcome these problems a framework is needed, one of which is TOGAF. TOGAF is a framework that has a set of supporting tools for developing enterprise architectures. TOGAF is a method that can be adapted to all changes and needs during planning. The purpose of this research is to get the gaps in the existing technology architecture and then provide recommendations in the form of the proposed technology architecture so that the existing gaps can be repaired and can run well. The results of this study found that to improve service to students, 7 application modules were needed and the need for improvements to the existing network at STMIK Amik Riau.